Safeguarding Lampung’s Migrant Workers: The Role of Siyasah Tanfidziyyah Syar’iyyah in Islamic Law-Based Protection Policies - Azizah, Khana; Zaelani, Abdul Qodir; Santoso, Rudi (Jurnal Ilmu Hukum Kyadiren, 2025)
This study examines the implementation of siyasah tanfidziyyah syar’iyyah in protecting migrant workers from Lampung, with a particular focus on the role of the Lampung Provincial Manpower Office. This concept refers to Islamic law-based policies aimed at achieving justice and welfare. Despite the existence of protective regulations, migrant workers remain vulnerable to exploitation. Using a qualitative approach with a case study method, this research collects data through interviews and documentation analysis. The findings reveal that the Manpower Office has implemented various policies, including counseling programs, agent verification, and cooperation with destination countries. However, significant challenges remain, particularly in monitoring illegal agents and ensuring post-return protection. This study recommends enhancing coordination, expanding training programs, and providing legal assistance to strengthen the protection of migrant workers in accordance with Islamic law principles.